Pengelompokan Obyek Wisata Potensial dengan Self Organizing Maps (SOM) dan Sum Additive Weighting (SAW) - Indra Dharma Wijaya; Muhammad Afif Hendrawan; Nurcahya Nania Anabela (JISKA (Jurnal Informatika Sunan Kalijaga), 2023)
Probolinggo Regency is an area in East Java that has tourism potential. The condition is seen from the many tourists visiting various attractions in Probolinggo Regency. To increase the number of tourist visits, it is necessary to develop tourism objects. However, not all attractions in Probolinggo Regency can be developed at the same time. This is due to budget limitations for tourism development. Therefore, it is necessary to have a grouping of attractions according to the priority level of development. In this study, researchers utilized Self Organizing Maps (SOM) and Sum Additive Weighing (SAW) methods to group attractions based on their development priority levels. SOM is used to determine groups of tourist objects based on the parameters of the number of domestic tourists, the number of foreign tourists, infrastructure, and the number of attractions. Furthermore, SAW is used to find out which group has the highest priority among other groups based on these parameters. To measure the quality of the resulting group, researchers used the value of the silhouette coefficient. Results from the grouping process resulted in three groups. Group C1 consists of 4 attractions, group C2 consists of 20 attractions, and group C3 consists of 10 attractions. The value of the silhouette coefficient also holds a good value, especially in group 1, which is 0.75006. Furthermore, based on the ranking of groups by the SAW method, the C1 group is the group of tourist attractions with the highest priority for development.